Aluminosilicates-Based Nanosorbents for Heavy Metal Removal – a Review - Arancibia-Miranda, N; Arancibia-Miranda, N (Elsevier B.V., 2024)
Contamination of water bodies with heavy metals poses a significant threat to human health and the environment, requiring the development of effective treatment techniques. In this context, aluminosilicates emerge as promising sorbents due to their cost-effectiveness and natural abundance. This review provides a clear, in-depth, and comprehensive description of the structure, properties, and characteristics of aluminosilicates, supporting their application as adsorbents and highlighting their diversity and adaptability to different matrices and analytes. Furthermore, the functionalization of these materials is thoroughly addressed, detailing the techniques currently used, exposing the advantages and disadvantages of each approach, and establishing comparisons and evaluations of the performances of various functionalized aluminosilicates in the extraction of heavy metals in aqueous matrices. This work aims not only to comprehensively review numerous studies from recent years but also to identify trends in the study of such materials and inspire future research and applications in the field of contaminant removal using aluminosilicates. © 2024 Elsevier B.V.